Quality of Life and Toxicity after SBRT for Organ-Confined Prostate Cancer, a 7-Year Study - Katz, Alan Jay; Kang, Josephine (Frontiers in Oncology, 2014)
Objectives: Stereotactic body radiation therapy (SBRT) yields excellent disease control for lowand intermediate-risk prostate cancer by delivering high doses of radiation in a small number of fractions. Our report presents a 7-year update on treatment toxicity and quality of life (QOL) from 515 patients treated with prostate SBRT. Methods: From 2006 to 2009, 515 patients with clinically localized, low-, intermediate- and high-risk prostate cancer were treated with SBRT using Cyberknife technology. Treatment consisted of 35 to 36.25 Gy in 5 fractions. Seventy-two patients received hormone therapy. Toxicity was assessed at each follow up visit using the Expanded Prostate Cancer Index Composite (EPIC) questionnaire and the Radiation Therapy Oncology Group (RTOG) urinary and rectal toxicity scale. Results: Median follow up was 72 months. The actuarial 7-year freedom from biochemical failure was 95.8%, 89.3% and 68.5% for low-, intermediate- and high-risk groups, respectively (p < 0.001). No patients experienced acute Grade III or IV acute complications. Fewer than 5% of patients had any acute Grade II urinary or rectal toxicity. Late toxicity was low, with Grade II rectal and urinary toxicity of 4% and 9.1%, respectively, and Grade III urinary toxicity of 1.7%. Mean EPIC urinary and bowel QOL declined at 1 month post-treatment, returned to baseline by 2 years and remained stable thereafter. EPIC sexual QOL declined by 23% at 6-12 months and remained stable afterwards. Of patients potent at baseline evaluation, 67% remained potent at last follow-up. Conclusions: This study suggests that SBRT, when administered to doses of 35 to 36.25 Gy, is efficacious and safe. With long-term follow up in our large patient cohort, we continue to find low rates of late toxicity and excellent rates of biochemical control.